2017
DOI: 10.1099/jgv.0.000799
|View full text |Cite
|
Sign up to set email alerts
|

A porcine enterovirus G associated with enteric disease contains a novel papain-like cysteine protease

Abstract: Identification of unknown pathogens in pigs displaying enteric illness is difficult due to the large diversity of bacterial and viral species found within faecal samples. Current methods often require bacterial or viral isolation, or testing only a limited number of known species using quantitative PCR analysis. Herein, faeces from two 25-day-old piglets with diarrhoea from Texas, USA, were analysed by metagenomic next-generation sequencing to rapidly identify possible pathogens. Our analysis included a bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Enteroviruses have been more generally linked to neurological disorders in pigs, although they are commonly found in feces as well 11,12,[32][33][34] . In a study from Vietnam, no significant correlation was found between diarrhea status and presence of enterovirus G in feces 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Enteroviruses have been more generally linked to neurological disorders in pigs, although they are commonly found in feces as well 11,12,[32][33][34] . In a study from Vietnam, no significant correlation was found between diarrhea status and presence of enterovirus G in feces 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The samples from these two cases were processed and submitted for library preparation and NGS on the Illumina MiSeq platform, using previously described methods (Jarvis et al., ). The raw data were analysed using in‐house NGS pipeline with custom bioinformatics tools (Knutson, Velayudhan, & Marthaler, ). Nucleotide and amino acid alignments were constructed using MAFFT in Geneious v9.1.8, and phylogenetic trees were built using PMYML with a GTR substitution model and bootstrapped with 500 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a previous study using reverse genetics revealed that the US EV‐G17‐PLCP strain functionally produces the exogenous PLCP gene in virus‐infected cells, demonstrating its own ALFQ↓GPPV and AEFQ↓GPPT sequences as the putative cleavage sites (Shang et al., ). Considering the sequence similarity of the putative cleavage sites including GPPT−ALFQ, GPPA−ALFQ, and GPPE−ALPQ among global strains (Conceição‐Neto et al., ; Knutson et al., ; Tsuchiaka et al., ), therefore, the cleavage of the inserted PLCP gene appears to be guaranteed using each corresponding cleavage sequence. Consistently, the recombinant ToV‐PLCP of the EV‐G KNU‐1811 strain is bordered by two analogous predicted 3C pro cleavage sites, ALFQ↓GPPV and AVFQ↓GPPT, at its N and C termini, respectively, indicating its proteolytic processing by 3C pro into a functional product (Figure a).…”
mentioning
confidence: 99%